(untitled) (Journal of Global Arts Studies, 2024)
Background: As a form of expression, "body" is the first and most direct medium of human beings. American pragmatism Schusterman attaches great importance to exploring the "body" of human beings, and put forward the theory of body aesthetics, emphasizing the importance of the body in human society. In the scene of diversified media symbiosis in modern society, the continuous innovation of technology makes the body as a medium extended in many aspects. Dance, as a kind of art of body movement, is the most intuitive expression of the "body" as the medium without using the "second tool". Objective: Under the theory of Schstmann body aesthetics, this paper explores the "amplification" and modern interpretation of the traditional dance body under the rendering of the image world. Methods: The author discusses the collision of dance image between dance body and technical means through the qualitative analysis method. Results: Through the analysis of the body presentation in dance image works, the connection with schstmann body aesthetics. Conclusion: Driven by the modern visual mechanism, the body, which carries physiological and natural attributes and carries social significance, shows a highly aestheticized trend.